Dampak Corporate Social Responsibility (CSR) dan Good Corporate Governance (GCG) Terhadap Nilai Perusahaan Sektor Energi yang Terdaftar di BEI periode 2019-2022 - Aftinah Wafa Ahmadi; Evi Yuniarti; Endah Yuni Puspitasari (Jurnal Riset Akuntansi, 2024)
This research aims to determine the impact of CSR and GCG on company value in energy sector companies listed on the IDX in 2019-2022. The population in this study are energy sector companies listed on the IDX. The sampling method used was a purposive sampling method based on certain criteria, resulting in 11 energy sector companies listed on the IDX. The data collection technique in this research uses secondary data. The data analysis carried out was carrying out classical assumption tests, carrying out multiple linear regression analysis and carrying out hypothesis testing using IBM SPSS Statistics version 26 software. The results of this research show that the three independent variables simultaneously influence company value. Partially, CSR variables and institutional ownership have an effect on company value, while managerial ownership variables have no effect on company value.